IMPLEMENTATION OF INQUIRY LEARNING IN ENGLISH FOR SECRETARY’S INSTRUCTIONAL MATERIAL THROUGH MOODLE - Raharjo, Didik Hariyadi; Mayuni, Ilza; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This research is aimed to know the condition of English for Secretary (EFS) teaching material at Secretarial Academy of Budi Luhur (ASTRI Budi Luhur), to develop EFS teaching material based on inquiry learning approach through e-learning Moodle and to know the effectiveness of EFS teaching material that is developed by the Researcher. The method that is used in this research is Research and Development, meanwhile the phases that are used in this research is Integrative Learning Design Framework (ILDF) phases. The validity of the product of this research is examined by using expert judgment. The result of this study shows that EFS instructional material that has been used in ASTRI Budi Luhur considered not feasible to be used in teaching EFS, therefore the researcher arrange an instructional material that is accordance with the needs of students ASTRI Budi Luhur. Based on the large group testing, the developed instructional material can be implemented well. And the result of the perception test that has been conducted to the user shows that the developed material is very feasible to use and it gives a good result in teaching learning process.